Eradicazione virus epatite C entro il 2030: quale sfida futura per i Ser.D.? - Cevola, Maria; Falvo, Antonella; Gallo, Rosalba; Lucchino, Pietro; Renda, Antonella; Saladino, Antonella; Audino, Giulia (Mission - Open Access, 2025)
Injecting drug users represent the largest reservoir of hepatitis C virus, with the prevalence in this subpopulation estimated to be between 30 and 60%. This group is also a source of contagion, as it is estimated that a substance user can infect 20 other people within the first three years. In order to expand as much as possible the population subject to screening within the Addiction Services, the Calabria Region proposes an evaluation of drug addicts, emphasizing the need to obtain reliable data on the share of injecting users and the extension of the program also to alcohol abusers and patients suffering from gambling disorder. This project involves the use of staff already in Service, as they already know the setting and the users. As part of the secondary prevention campaign, several phases are outlined: 1. Identify the screening target. 2. Offer of the screening test: acquisition of consent/dissent. 3. Test execution. 4. Follow up and post-test counselling.